2021
DOI: 10.3390/v13050839
|View full text |Cite
|
Sign up to set email alerts
|

HIV Protease: Historical Perspective and Current Research

Abstract: The retroviral protease of human immunodeficiency virus (HIV) is an excellent target for antiviral inhibitors for treating HIV/AIDS. Despite the efficacy of therapy, current efforts to control the disease are undermined by the growing threat posed by drug resistance. This review covers the historical background of studies on the structure and function of HIV protease, the subsequent development of antiviral inhibitors, and recent studies on drug-resistant protease variants. We highlight the important contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 84 publications
0
33
0
1
Order By: Relevance
“…In general, we found that the HIVpr and VIRpr substitution models decreased (compared with the HIVb model) most of relative rates of change among the amino acids considering the PR function, which suggests a higher specificity. For example, the PR presents a catalytic aspartic acid (Asp-25) that is usually conserved due to selection to maintain the protein function [ 46 , 47 ]. Consequently, if it is not conserved, it could only change to glutamic acid (also a potent acidic nucleophile) in order to conserve the physicochemical properties and functionality of the catalytic region.…”
Section: Resultsmentioning
confidence: 99%
“…In general, we found that the HIVpr and VIRpr substitution models decreased (compared with the HIVb model) most of relative rates of change among the amino acids considering the PR function, which suggests a higher specificity. For example, the PR presents a catalytic aspartic acid (Asp-25) that is usually conserved due to selection to maintain the protein function [ 46 , 47 ]. Consequently, if it is not conserved, it could only change to glutamic acid (also a potent acidic nucleophile) in order to conserve the physicochemical properties and functionality of the catalytic region.…”
Section: Resultsmentioning
confidence: 99%
“…HAART changed HIV infection from a fatal to a chronic manageable disease, although the virus remains integrated in host cells. To minimize the risk of evolution of drug-resistant variants [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], sophisticated drug combinations and the precise dosage are important [ 83 , 84 , 85 ]. The treatment in individual patients must sometimes be changed not only due to the development of drug resistance but also due to unwanted side effects appearing after long-term therapy [ 86 ].…”
Section: Rna Virusesmentioning
confidence: 99%
“…All nine HIV protease inhibitors in clinical use (saquinavir, indinavir, ritonavir, nelfinavir, amprenavir, lopinavir, tipranavir, atazanavir, and darunavir) target the active site [ 17 , 79 ] of the HIV protease, although it has been suggested that darunavir [ 87 ] and tipranavir [ 88 ] may also block dimerization via a secondary binding site ( Figure 3 ). It has been shown that all these inhibitors have an affinity for the precursor, which is of several orders of magnitude lower than the affinity for its mature form [ 89 , 90 , 91 , 92 ].…”
Section: Rna Virusesmentioning
confidence: 99%
“…This paper is dedicated to the loving memory of Dr. Stephen Oroszlan, who made an essential contribution to retrovirology, including the field of HIV protease and other retroviral proteases [ 27 , 28 , 29 ]. Our research group, the Laboratory of Retroviral Biochemistry was established at the University of Debrecen in 1992 by József Tőzsér, after working together with Dr. Oroszlan in the Molecular Virology and Carcinogenesis Laboratory at NCI-Frederick Center for Cancer Research.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group, the Laboratory of Retroviral Biochemistry was established at the University of Debrecen in 1992 by József Tőzsér, after working together with Dr. Oroszlan in the Molecular Virology and Carcinogenesis Laboratory at NCI-Frederick Center for Cancer Research. Most studies of our research group followed his ideas, including the investigation of HIV-1 and other retroviral proteases, antiviral inhibitors and enzyme specificity, works which have been covered by reviews [ 25 , 27 , 30 ]. Several studies of our research group—including the present work—were inspired by the specificity studies of our laboratory performed previously together with Dr. Oroszlan and his colleagues.…”
Section: Introductionmentioning
confidence: 99%